Targeting Transporters for Drug Delivery to the Brain: Can We Do Better? - Elena Puris; Gert Fricker; Mikko Gynther (2022)
Abstract Limited drug delivery to the brain is one of the major reasons for high failure rates of central nervous system (CNS) drug candidates. The blood–brain barrier (BBB) with its tight junctions, membrane transporters, receptors and metabolizing enzymes is a main player in drug delivery to the brain, restricting the entrance of the drugs and other xenobiotics. Current knowledge about the uptake transporters expressed at the BBB and brain parenchymal cells has been used for delivery of CNS drugs to the brain via targeting transporters. Although many transporter-utilizing (pro)drugs and nanocarriers have been developed to improve the uptake of drugs to the brain, their success rate of translation from preclinical development to humans is negligible. In the present review, we provide a systematic summary of the current progress in development of transporter-utilizing (pro)drugs and nanocarriers for delivery of drugs to the brain. In addition, we applied CNS pharmacokinetic concepts for evaluation of the limitations and gaps in investigation of the developed transporter-utilizing (pro)drugs and nanocarriers. Finally, we give recommendations for a rational development of transporter-utilizing drug delivery systems targeting the brain based on CNS pharmacokinetic principles.